Mind the working-class people! an African reading of Leviticus 25:8-55 with Latino/a critical tools - Mtshiselwa, Ndikho (Old Testament essays, 2016)
It is generally accepted by Latino/a biblical scholars, namely, Fernando F. Segovia and Alejandro F. Botta, among others, that both the historical-critical methods and the contextual approaches are equally important in the reading of the HB. First, this paper argues that Lev 25:8-55 contains verses (cf. Lev 25:10, 39-40 and 54-55) which are ascribed to the Deuteronomistic writers (D) but which were re-used by the authors of the Holiness Code (H). Second, because the absolute noun, רּפּשּׂ "hired labourer" and the qal verb, לּבֿץ "to work" in Lev 25:40 refer to the working-class people, the context(s) from which the text of Lev 25:8-55 emerged will be investigated in relation to the working-class people. Third, the paper probes the relevance of Lev 25:8-55 to Ernesto "Che" Guevara's discourse of the experiences of the working-class people and Segovia's reading of the HB in the light of such experiences. It is argued in this paper that H's concern for social justice for the working-class people can throw light on the reading of the ancient texts, particularly from the perspective of the Latino/a biblical criticism, and more importantly, that such a reading could also have implications for the working-class people of South Africa.